REPRODUCTIVE BIOLOGY OF THE VENEZUELA ROUND STINGRAY Urotrygon venezuelae SCHULTZ FROM THE COLOMBIAN CARIBBEAN (2015)
As for most batoid species, little is known about the basic biology of the Venezuela round stingray Urotrygon venezuelae (Urotrygonidae). This study presents information about the reproductive biology of the species, including fecundity, embryonic development stage, relationship between maternal size and fecundity, gonadosomatic (GSI) and hepatosomatic (HSI) indices, sex ratios, maturity size and size at birth. With all this information, a preliminary reproductive cycle is proposed. A total of 269 specimens were caught with beach seine in Salguero beach, Colombian Caribbean Sea, between August 2005 and October 2006. We propose for U. venezuelae a biological cycle with three reproductive peaks: November-December, March-April and August. Median sexual maturity size was calculated in 176 mm (total length) for females and 227 mm for males; fecundity ranged between one and six embryos per female. We found that cloacal diameter and liver weight were better predictors for fecundity than total length for U. venezuelae.